Abundance retrieval of hydrous minerals around the Mars Science Laboratory landing site in Gale crater, Mars. (February 2016) - Lin, Honglei; Zhang, Xia; Shuai, Tong; Zhang, Lifu; Sun, Yanli
Abstract: The detection of hydrous minerals on Mars is of great importance for revealing the early water environment as well as possible biotic activity. However, few studies focus on abundance retrieval of hydrous minerals for some difficulties. In this paper, we studied the area around the Mars Science Laboratory (MSL) landing site, to identify hydrous minerals and retrieve their abundance. Firstly, the distribution of hydrous minerals was extracted using their hydration features. Then, a sparse unmixing algorithm was applied along with the CRISM spectral library to retrieve the abundance of hydrous minerals in this area. As a result, seven hydrous minerals were retrieved, i.e. actinolite, montmorillonite, saponite, jarosite, halloysite, szomolnokite and magnesite and, the total concentration of all hydrous minerals was as high as 40 vol% near the lower reaches of Mount Sharp. Our results were consistent with results from related research and the in-situ analysis of the MSL rover Curiosity. Highlights: An abundance retrieval strategy combining feature extraction with sparse unmixing algorithm is proposed for Mars hydrous minerals. Seven hydrous minerals are retrieved around the Mars Science Laboratory landing site. The most abundant mineral is actinolite with an abundance as high as almost 30 vol%. The proposed method has good prospects for wide use for quantitative mineralogical mapping at the global scale of Mars.